Neurodegenerative Diseases Molecular Mechanisms and Current Therapeutic Approaches - Ersoy Tunalı, Nagehan (IntechOpen, 2021)
Neurodegenerative diseases represent a very large group of heterogeneous disorders affecting specific subtypes of neurons in the brain. This book contributes insight both to the awareness of the brain and its neurodegenerative states. The chapters present current knowledge regarding genetics, molecular mechanisms, and new therapeutic strategies against neurodegenerative disorders. The book is intended to serve as a source to aid clinicians and researchers in the field, and also life science readers to increase their understanding and awareness of the clinical correlations, genetic aspects, neuropathological findings, and current therapeutic interventions in neurodegenerative diseases. I believe that this book will enlighten the curiosity for neurodegeneration and also encourage researchers to work on potentially effective molecular therapies for still mysterious neurodegenerative disorders.